Method for analyzing shear strength of coal slurry fusion body based on three-dimensional scanning

Through the combination of three-dimensional scanning and variable angle shear test, the problems of repeatability and intersection in the morphology of the fault surface of coal rock mass were solved, and the shear strength and morphology of the coal slurry fusion were accurately quantified and evaluated.

CN119595458APending Publication Date: 2025-03-11SHANGHAI DATUN ENERGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411736000.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art has repetition and intersectionality in the morphological characterization of the fault surface of coal rock mass, and it is difficult to streamline and accurately reflect the roughness and undulation characteristics of the fault surface of coal rock mass.

Method used

The three-dimensional scanning analysis method was used to perform variable angle shear test and three-dimensional scanning on the coal slurry fusion, and combined with the root mean square deviation Z value of the two-dimensional profile as an evaluation index, the three-dimensional morphological characteristics and shear strength of the fracture surface were quantified.

Benefits of technology

It effectively reflects the discretency and fluctuation of the fracture surface morphology, and provides an accurate and reliable method for the evaluation of the fracture surface morphology of coal rock samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595458A_ABST
    Figure CN119595458A_ABST
Patent Text Reader

Abstract

The invention discloses a method for analyzing the shear strength of a coal slurry fusion body based on three-dimensional scanning, which comprises the following steps: S1, carrying out a variable-angle shear test on a coal slurry fusion body sample, and analyzing the shear strength characteristic and the damage characteristic of the coal slurry fusion body; s2, scanning the crushed coal slurry fusion body by using a three-dimensional scanner to obtain a three-dimensional model diagram of the fracture surface of the coal slurry fusion body; and S3, analyzing the three-dimensional morphology characteristics of the fracture surface of the coal slurry fusion body according to the three-dimensional model diagram of the fracture surface of the coal slurry fusion body, quantifying the three-dimensional morphology characteristics, and determining the shear strength characteristics of the coal slurry fusion body. According to the method, three-dimensional scanning is combined with a variable-angle shear test method, the shear strength characteristic of the coal slurry fusion body is quantified, meanwhile, the root-mean-square deviation Z value of a two-dimensional section is used as an evaluation index, discreteness and volatility of the fracture surface morphology can be effectively reflected, and an effective method is provided for coal rock mass sample fracture surface morphology evaluation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal mining, and in particular to a method for analyzing the shear strength of a coal slurry fusion body based on three-dimensional scanning. Background Art

[0002] In the field of fracture surface morphology evaluation of coal and rock samples, many domestic and foreign scholars have proposed a variety of methods for quantitative characterization of parameters, which mainly include the roughness coefficient method (JRC), the fractal dimension method and the mathematical statistics method. Among them, JRC is to establish an empirical formula for analysis based on the empirical statistical method; the fractal dimension method is to analyze different fracture surface roughness using different fractal dimension measurement methods. Different fractal methods may produce different fractal dimension value results. Both methods are controversial. The mathematical statistics method is to quantitatively characterize the morphological characteristics of the roughness of the fracture surface based on different statistical parameters of the fracture surface profile. The specific fracture surface profile statistical parameters include but are not limited to the root mean square RMS of the fracture surface profile height, the mean value of the profile height CLA, the first-order derivative ZV and the second-order derivative Z3 of the RMS, the maximum and minimum profile height difference, the ratio between the mean values ​​of the profile height Z4, the square value MSV of the profile height, the autocorrelation function ACF and the structure function SF, etc.

[0003] In summary, a lot of research results have been achieved on the parameters and methods for characterizing the surface fracture morphology of coal and rock masses, but there are obvious repeatability and overlap between different quantitative characterization methods. Therefore, it is particularly necessary to study a parameter that is as concise as possible and can accurately reflect and characterize the roughness and undulation characteristics of the fracture surface morphology of coal and rock masses. Summary of the invention

[0004] In view of the above-mentioned technical deficiencies, the purpose of the present invention is to provide a method for analyzing the shear strength of coal slurry fusion body based on three-dimensional scanning.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: The present invention provides a method for analyzing the shear strength of a coal slurry fusion body based on three-dimensional scanning, comprising the following steps: S1. Conduct variable angle shear test on coal slurry fusion body specimens to analyze the shear strength characteristics and failure characteristics of the coal slurry fusion body; S2. Scanning the crushed coal slurry fusion body with a three-dimensional scanner to obtain a three-dimensional model diagram of the fracture surface of the coal slurry fusion body; S3. Analyze and quantify the three-dimensional morphological characteristics of the fracture surface of the coal slurry fusion body based on the three-dimensional model diagram of the fracture surface of the coal slurry fusion body to determine the shear strength characteristics of the coal slurry fusion body.

[0006] Preferably, step S1 includes: S1.1. Prepare coal slurry fusion samples with different coal content and water-cement ratio; S1.2. Use the variable angle shear method to conduct shear tests on the specimens, apply statistical and static methods to accurately calculate the normal stress and tangential stress data on the shear surface, and draw a relationship curve; S1.3. Analyze the test cohesion and internal friction angle parameters based on the relationship curve.

[0007] Preferably, step S2 includes: S2.1. Scan the fracture surface of the coal slurry fusion body sample using a three-dimensional scanner to obtain three-dimensional point cloud data of the fracture surface; S2.2. Use WandStudioPro software to perform 3D reconstruction to obtain a 3D model of the fracture surface. Import the model data into Rhino 6 software, extract the points and export them as a csv file.

[0008] Preferably, step S3 includes: S3.1. Use Surfer 15 software to process the collected point cloud data in detail, and use the Kriging spatial autocovariance interpolation method to draw a three-dimensional wireframe map and contour map of the fracture surface; S3.2. Analyze the differences in fracture surface morphology of samples with different coal content and water-cement ratio after destruction at different shear angles based on the three-dimensional wireframe diagram and contour diagram.

[0009] Preferably, the method further includes the following steps: selecting a statistical parameter method to statistically analyze parameters reflecting changes in the fracture surface morphology of the coal slurry fusion body, and introducing the root mean square deviation Z value of the two-dimensional profile as an evaluation index for the discreteness and volatility of the fracture surface morphology.

[0010] The beneficial effects of the present invention are as follows: the present invention utilizes three-dimensional scanning combined with a variable angle shear test method to quantify the shear strength characteristics of a coal slurry fusion body, and simultaneously utilizes the root mean square deviation Z value of a two-dimensional profile as an evaluation index, which can effectively reflect the discreteness and volatility of the fracture surface morphology, and provides an effective method for evaluating the fracture surface morphology of coal rock samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1 This is a shear stress-strain curve diagram of a coal slurry fusion body with a coal content of 0g in an embodiment of the present invention; Figure 2 This is a shear stress-strain curve diagram of a coal slurry fusion body with a coal content of 600g in an embodiment of the present invention; Figure 3 This is a graph showing shear stress and normal stress of an unmixed coal sample in an embodiment of the present invention; Figure 4 It is a normal stress and shear stress curve diagram of a 600g coal-blended sample in an embodiment of the present invention; Figure 5 This is a surface crack evolution diagram of shear failure of a coal slurry fusion body in an embodiment of the present invention; Figure 6 This is a diagram of the internal morphology of the sample after shear test failure in the embodiment of the present invention; Figure 7 The three-dimensional scanning processing effect of the fracture surface of each sample in the embodiment of the present invention; Figure 8 The fracture surface morphology cloud diagram of the sample with 0g and 600g coal content in the embodiment of the present invention; Fig. 9 This is a cloud diagram of the fracture surface morphology of a sample with a coal content of 400g and a water-cement ratio of 0.4:1 in an embodiment of the present invention; Fig.10 Schematic diagram of fracture surface morphology data extraction in an embodiment of the present invention; Fig.11 It is a cross-sectional view of the fracture surface of the coal slurry fusion body sample in the embodiment of the present invention. DETAILED DESCRIPTION

[0013] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] Example A method for analyzing the shear strength of a coal slurry fusion body based on three-dimensional scanning comprises the following steps: S1.1. Prepare 24 100mm×100mm×100mm coal slurry fusion samples with coal content of 400g and 600g and water-cement ratio of 0.4:1 and 0.6:1, including 15 samples with coal (J600, J400, J0.4) and 9 samples without coal (J0). The sample parameters are shown in Table 1. Table 1: Sample parameters with different coal content and water-cement ratio

[0015] S1.2. The shear test of the sample was carried out by using the variable angle shear method. The normal stress and tangential stress data on the shear surface were accurately calculated by using the statistical and static methods. The relationship curve was drawn to analyze the shear strength characteristics and failure characteristics of the coal slurry fusion body. The test equipment used the WDW-300 microcomputer-controlled electronic universal testing machine as the shear device. Its loading force measurement range covers 0-300kN and the full automatic shifting function ensures the smooth progress of the test. In terms of speed, the testing machine has an adjustment range of 0-500mm / min. This test specially selected a loading rate of 0.5mm / min. (1) Analysis of shear strength characteristics The variable angle shear method is a test method that uses an electronic universal testing machine to apply a vertical load to the sample. Through the variable angle shear fixture, it is easy to switch between different shear angles, thereby simulating a variety of actual working conditions. During the experiment, the statistical and static methods are used to accurately calculate the normal stress and tangential stress on the shear surface. Based on these data, the corresponding relationship curve is drawn, and then the key mechanical parameters such as the cohesion and internal friction angle of the sample are deeply analyzed; Figure 1 The shear stress-strain curve of coal slurry with 0g coal content, Figure 2 The shear stress-strain curve of the coal slurry fusion body with a coal content of 600g can be seen from the test curve. The shear stress-strain curves obtained from the test results all have obvious peaks, and the shear stress peaks tested under different shear angles and different coal content are different. Taking the coal content of 0g and the shear angle of 50° as an example, the change law of shear stress during the shearing process of the coal slurry fusion sample is similar to that of ordinary rocks. The loading process can be roughly divided into three stages: there is a pore compaction stage at the beginning of the shear displacement. In this stage, the shear stress increases with the shear strain. The microcracks inside the sample are gradually closed and compacted. The strain in this section is only about 0.005; with the increase of shear displacement, the shear stress increases rapidly, which is a linear elastic change stage, and when the shear strain reaches about 0.03-0.04, the shear stress peak value appears. This peak value is the peak shear strength of the coal slurry fusion sample; with the further increase of shear displacement, the shear stress-strain curve shows a rapid decrease in shear stress, and then the shear stress decrease rate slows down. At this time, the entire shear surface cracks penetrate, and the sample is completely sheared and loses its bearing capacity. The shear stress-strain curve characteristics of most samples in the test are as described above, but due to different conditions such as coal content and shear angle, the shear curves of different samples are also different; From the test results, it can be seen that the shear stress-strain curve of the coal slurry fusion body also has the following characteristics. First, as the shear angle increases, the peak shear stress strength of the sample gradually decreases. The average shear stress peaks of the sample with 0g coal content at 50°, 60°, and 70° are 6.69MPa, 4.82MPa, and 3.56MPa, respectively. When the shear angle increases from 50° to 70°, the shear stress peak strength decreases by 46.79%; the average shear stress peaks of the sample with 600g coal content at 50°, 60°, and 70° are 5.26MPa, 3.87MPa, and 1.98MPa, respectively. When the shear angle increases from 50° to 70°, the shear stress peak strength decreases by 62.35%. Second, as the amount of coal in the sample increases, the peak shear stress strength of the sample gradually decreases. When the coal content increases from 0g to 600g, the average shear stress peaks at 50°, 60°, and 70° decrease by 21.37%, 19.70%, and 44.38%, respectively. From the reduction range, it can be seen that the increase in shear angle has a greater impact on the peak strength test results of the sample; S1.3. Analyze the cohesion and internal friction angle parameters of the test based on the relationship curve: (2) Analysis of internal friction angle and cohesion Cohesion of coal slurry fusion samples , internal friction angle Calculate using the following formula: ; Where: ——Coal slurry fusion cohesion, unit is MPa; ——internal friction angle of coal slurry fusion body, in degrees; Figure 3 is the shear stress and normal stress curve of the unmixed coal sample. Figure 4 The normal stress and shear stress curve of 600g coal-blended sample is shown in Figure 2. Figure 3 , Figure 4 It can be seen that the cohesion of the sample decreases with the addition of crushed coal, from 2.60MPa to 1.52MPa; on the contrary, the internal friction angle of the sample increases with the increase of coal content, from 36.84° to 41.47°. The statistical results of the shear test are shown in Table 2; Table 2: Shear test results

[0016] (3) Evolution mode of shear surface cracks in coal slurry fusion ①Surface cracks The shear failure characteristics of coal slurry amalgam reflect the shear mechanical properties of the coal slurry amalgam as a whole to a certain extent. Figure 5As shown in the figure, under the action of shear load, the sample undergoes the compaction stage, the linear change stage and the yield failure stage. The actual failure surface of the sample is not an ideal plane, but is generated and developed along the shear surface and the position of the coal sample inside the coal slurry fusion. The test found that the failure characteristics of the coal slurry fusion samples with different shear angles are different. When the shear angle is 50°, the secondary cracks generated on the shear surface intersect and penetrate the main cracks, the main cracks and secondary cracks have a wider development range and more stripes, and the shear surface is broken and detached, and the degree of crushing of the sample is more obvious; when the shear angle is 60°, the degree of crushing is attenuated, two main cracks are generated on the shear surface, and there are fewer secondary cracks, and no obvious crushing and detaching phenomenon occurs; when the shear angle is 70°, there is no crushing or detaching on the fracture surface, and only one obvious fracture line. Comparing the failure of samples with different shear angles, it can be seen that the smaller the shear angle, the wider the development range of the main cracks and secondary cracks, the more stripes, and the more obvious the phenomenon of crushing and detaching caused by friction dislocation and crack penetration.

[0017] ②Internal damage form Figure 6 This is the internal morphology of the sample after shear test failure. Figure 6 It can be seen that after shear failure, the sample is roughly broken into two parts along the fracture surface, and the two parts have a certain symmetry. When the sample is broken, the crushed coal mixed inside the sample is also divided into two parts along the fracture surface after shear loading, and is respectively bonded to the two parts of the slurry stone body. This phenomenon shows that the strength of the sample after coal slurry fusion is much greater than the strength of the coal body, and the bonding strength of the coal slurry fusion interface is also greater than the strength of the coal body, so the internal coal body is not completely separated like "breaking a peach"; at the same time, the internal coal body of the sample is broken into fragments and powder, which also proves that the strength of the coal slurry fusion body and its bonding interface is much greater than the strength of the coal body; S2.1. Take a coal slurry fusion sample and scan the fracture surface with a 3D scanner to obtain the 3D point cloud data of the fracture surface. Use WandStudioPro software to perform 3D reconstruction to obtain a 3D model of the fracture surface. Import the model data into Rhino 6 software to extract points and export csv files. Use Surfer 15 software to process the collected point cloud data. Use Kriging spatial autocovariance interpolation method to draw 3D wireframe diagrams and contour maps of the fracture surface. The 3D scanning processing effects of the fracture surfaces of each sample are as follows: Figure 7 As shown; The fracture surfaces of different samples were scanned by a 3D scanner, and 3D cloud maps were drawn based on the Kriging spatial autocovariance interpolation method, such as Figure 8As shown. From the distribution of the cloud maps of each sample, it can be seen that there are differences in the fracture surface morphology after the samples with different shear angles, different coal content and different water-cement ratios are damaged. From the three shear angle cloud maps numbered J0, it can be seen that when the shear angle of the sample is 50°, the maximum fluctuation height of the fracture surface morphology of the sample can reach 69.15mm, and the blue area in the cloud map (fluctuation less than 10mm) is small; when the shear angle is 60°, the maximum fluctuation height of the fracture surface can reach 48.51mm; when the shear angle is 70°, the maximum fluctuation height of the fracture surface is 42.55mm, but the fluctuation height of most areas of the fracture surface is below 24mm. The result shows that as the shear angle increases, the fluctuation of the fracture surface morphology of the sample decreases, and the attenuation ratio from 50° to 70° is 38.47%. Three shear angles of No. J600: When the shear angle of the sample is 50°, it can be seen from the cloud map that the maximum fluctuation height of the sample fracture surface morphology can reach 45.09mm, and the fluctuation in the middle area of ​​the fracture surface is relatively large. When the shear angle is 60°, the maximum fluctuation height of the fracture surface can reach 62.44mm. The maximum position appears at the edge of the sample. Considering that the edge damage and tilt caused by the example, the fluctuation height of the rest of the fracture surface is less than 35mm; when the shear angle is 70°, the maximum fluctuation height of the fracture surface is 27.13mm. The attenuation ratio of the fracture surface fluctuation height from 50° to 70° is 39.83%, which is not much different from the former. from Fig. 9 It can be seen that when the shear angle of the sample with a coal content of 400g is 50°, the maximum fluctuation height of the sample fracture surface is 76.85mm, the fluctuation in the middle area of ​​the fracture surface is large, and the maximum drop is 40mm; when the shear angle is 60°, the maximum fluctuation height of the fracture surface is 55.01mm, and the fluctuation height of most areas of the fracture surface is greater than 10mm; when the shear angle is 70°, the maximum fluctuation height of the fracture surface is 28.22mm. The attenuation ratio of the fracture surface fluctuation height from 50° to 70° is 63.27%. When the shear angle of the sample with a water-cement ratio of 0.4:1 is 50°, the maximum fluctuation height of the sample fracture surface morphology is 46.07mm, the fluctuation in the middle area of ​​the fracture surface is large, and the entire fracture surface changes from high to low and then to high; when the shear angle is 60°, the maximum fluctuation height of the fracture surface is 50.07mm, but the maximum position appears at the edge of the sample and the fluctuation height in most areas of the fracture surface is less than 44mm; when the shear angle is 70°, the maximum fluctuation height of the fracture surface is 44.76mm. The attenuation ratio of the fracture surface fluctuation height from 50° to 70° is 2.97%. The increase in the shear angle of the sample under this water-cement ratio has little effect on the fluctuation change of the fracture surface morphology; S3.1. The statistical parameter method is used to statistically reflect the parameters of the changes in the fracture surface morphology of the coal slurry fusion body; in order to more accurately describe the morphological characteristics of the fracture surface, this paper introduces the root mean square deviation Z value of the two-dimensional profile as an evaluation index. This indicator is not only closely related to the position of each measuring point, but also shows a high sensitivity to the height value at the measuring point (whether too large or too small). Therefore, it can effectively reflect the discreteness and volatility of the fracture surface morphology. Specifically, the larger the Z value, the higher the degree of fluctuation of the fracture surface; conversely, the smaller the Z value, the relatively smooth fracture surface morphology. The calculation formula of Z using the statistical parameter method is: ; Where: The number of coordinate points selected for the 2D section; The spacing of sample points along the x direction is 0.2 mm; is the coordinate of the sample point on the curve; The 3D wireframe diagram of the crack was obtained by 3D scanning technology, and then a crack surface on or below the sample was selected for analysis. In order to better understand the structure of the crack surface, the sample was divided along the x-axis and y-axis directions, and vertical interception was performed along the center line of the x-axis and y-axis to obtain a 2D cross-sectional diagram of the crack surface. Fig.10 As shown. The coordinate points of the crack contour line were selected from the intercepted x-axis and y-axis profiles, and a sampling interval of 0.2 mm was set. The coordinate data of the two contour profile curves were substituted into the above formula for calculation, thereby obtaining the Z value reflecting the morphological characteristics of the crack surface; The RMS deviation of the fracture surface of the coal slurry fusion body is shown in Table 3. Fig.11 It can be seen that when the shear angle is 50°, the root mean square deviation Z value of the coal slurry fusion fracture surface is 8.12-16.83; when it is 60°, the Z value is 4.63-13.91; when it is 70°, the Z value is 1.75-5.90. The root mean square deviation of the fracture surface in the x-axis and y-axis directions at the same shear angle is not much different, that is, the fluctuation difference of the fracture surface in the x-axis direction and the y-axis direction is not much. As the shear angle increases, the root mean square deviation Z value of the fracture surface decreases; Table 3: RMS deviation Z value of fracture surface of coal slurry fusion specimen

[0018] In summary: (1) With the increase of shear angle, the peak shear stress intensity of the sample gradually decreases. The average peak shear stress of the sample with 0g coal content at 50°, 60° and 70° are 6.69MPa, 4.82MPa and 3.56MPa respectively. When the shear angle increases from 50° to 70°, the peak shear stress intensity decreases by 46.79%. The average peak shear stress of the sample with 600g coal content at 50°, 60° and 70° are 5.26MPa, 3.87MPa and 1.98MPa respectively. When the shear angle increases from 50° to 70°, the peak shear stress intensity decreases by 62.35%.

[0019] (2) As the amount of coal added to the sample increases, the peak shear stress strength of the sample gradually decreases. When the amount of coal added increases from 0g to 600g, the average shear stress peaks at 50°, 60°, and 70° decrease by 21.37%, 19.70%, and 44.38%, respectively. From the reduction range, it can be seen that the increase in shear angle has a greater impact on the peak strength test results of the sample. As the cohesion of the sample decreases after the addition of crushed coal, it decreases from 2.60MPa to 1.52MPa; on the contrary, the internal friction angle of the sample increases with the increase in the amount of coal added, increasing from 36.84° to 41.47°.

[0020] (3) There are differences in the fracture surface morphology of samples with different shear angles, different coal content, and different water-cement ratios after damage. As the shear angle increases, the root mean square deviation Z value of the fracture surface decreases. When the shear angle is 50°, the root mean square deviation Z value of the fracture surface of the coal slurry fusion is 8.12-16.83; when the shear angle is 60°, the Z value is 4.63-13.91; when the Z value is 70°, the Z value is 1.75-5.90. The root mean square deviation of the fracture surface in the x-axis and y-axis directions at the same shear angle is not much different, that is, the fluctuation of the fracture surface in the x-axis direction and the y-axis direction is not much different.

[0021] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for analyzing the shear strength of coal slurry fusion based on three-dimensional scanning, characterized in that: The following steps are involved: S1. Conduct variable angle shear test on coal slurry fusion body specimens to analyze the shear strength characteristics and failure characteristics of the coal slurry fusion body; S2. Scanning the crushed coal slurry fusion body with a three-dimensional scanner to obtain a three-dimensional model diagram of the fracture surface of the coal slurry fusion body; S3. Analyze and quantify the three-dimensional morphological characteristics of the fracture surface of the coal slurry fusion body based on the three-dimensional model diagram of the fracture surface of the coal slurry fusion body to determine the shear strength characteristics of the coal slurry fusion body.

2. The method for analyzing the shear strength of coal slurry fusion body based on three-dimensional scanning according to claim 1, characterized in that: Step S1 includes: S1.

1. Prepare coal slurry fusion samples with different coal content and water-cement ratio; S1.

2. Use the variable angle shear method to conduct shear tests on the specimens, apply statistical and static methods to accurately calculate the normal stress and tangential stress data on the shear surface, and draw a relationship curve; S1.

3. Analyze the test cohesion and internal friction angle parameters based on the relationship curve.

3. The method for analyzing the shear strength of coal slurry fusion body based on three-dimensional scanning according to claim 1, characterized in that: Step S2 includes: S2.

1. Scan the fracture surface of the coal slurry fusion body sample using a three-dimensional scanner to obtain three-dimensional point cloud data of the fracture surface; S2.

2. Use WandStudioPro software to perform 3D reconstruction to obtain a 3D model of the fracture surface. Import the model data into Rhino 6 software, extract the points and export them as a csv file.

4. The method for analyzing the shear strength of coal slurry fusion body based on three-dimensional scanning according to claim 1, characterized in that: Step S3 includes: S3.

1. Use Surfer 15 software to process the collected point cloud data in detail, and use the Kriging spatial autocovariance interpolation method to draw a three-dimensional wireframe map and contour map of the fracture surface; S3.

2. Analyze the differences in fracture surface morphology of samples with different coal content and water-cement ratio after destruction at different shear angles based on the three-dimensional wireframe diagram and contour diagram.

5. The method for analyzing the shear strength of coal slurry fusion body based on three-dimensional scanning according to claim 4, characterized in that: The following steps are also included: The statistical parameter method is used to statistically analyze the parameters that reflect the changes in the fracture surface morphology of the coal slurry fusion body, and the root mean square deviation Z value of the two-dimensional profile is introduced as an evaluation index for the discreteness and volatility of the fracture surface morphology.